The Role of Mental Health Literacy Education and Self-Stigma in Shaping Help-Seeking Intentions among Male Santri - Abidah El-Mukhayyarah; Fara Ulfa; Yuli Widiningsih; Indah Puji Ratnani (Universitas Negeri Padang, 2025)
There are many factors that can reduce the quality of learning in Islamic boarding schools (pondok pesantren), one of which is mental health issues. Cases such as bullying, juvenile delinquency, and depression among students are examples of problems that need attention to ensure that students have the knowledge to help themselves or others when needed. This study aims to explore the role of mental health literacy and self-stigma in shaping help-seeking intentions among male students at Pondok Pesantren X in Pekanbaru City. Low mental health literacy and the internalization of negative perceptions can lead to poor ability to recognize mental health problems, the development of inappropriate beliefs and attitudes toward mental health issues, and ineffective help-seeking behaviors. Through purposive sampling techniques, 84 male students were selected as research subjects. Data collection was conducted using the TPB Questionnaire, the Mental Health Literacy Scale (MHLS), and the Self-Stigma of Seeking Help (SSOSH). The results of multiple regression analysis showed F = 19.880 (p = 0.00) with an R Square value of 0.329. This indicates that mental health literacy and self-stigma simultaneously contribute to help-seeking intentions with a contribution rate of 32.9%. It can be concluded that male students with good mental health literacy and low self-stigma are more likely to have strong intentions to seek help.